PENGARUH INTENSITAS GAME ONLINE MOBILE LEGENDS TERHADAP MINAT BELAJAR SISWA KELAS V SD NEGERI 1 BANGUN KABUPATEN BUTON SELATAN - Yuan, Sri Yulan; Abdul rahim; Muhammad Ridwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of intensity of playing Mobile Legends online game and the learning interest of fifth-grade students at SD Negeri 1 Bangun, South Buton Regency, as well as to examine the influence between the two variables. This study employed a quantitative approach using a correlational survey method. The sample consisted of 15 students selected through a saturated sampling technique. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability, then analyzed using descriptive statistics and simple linear regression. The results showed that the intensity of playing Mobile Legends online game among students was in the high category, while student learning interest was in the low category. The simple linear regression test produced a significance value below 0.05, indicating a significant negative influence of Mobile Legends online game playing intensity on student learning interest, with a coefficient of determination ranging from 30% to 50%. This means that the higher the intensity of playing online games, the lower the student learning interest. These findings have direct implications for the achievement of SDGs Goal 4 on quality and equitable education, given that the degradation of learning interest at elementary school age threatens the quality of human resources in the long term.